Annatto-enriched egg improves the perception of satiety in healthy adults¿randomized clinical trial: EGGANT Study (2024)
ABSTRACT: Diet is one of the factors that prevents the development and death from cardiovascular diseases (CVD). It has been proposed that diets high in protein, which increase satiety, and with a high content of antioxidants, help reduce cardiovascular risk factors. The egg is one of the foods that produces greater satiety and provides antioxidants. In addition, due to its lipophilic matrix, it could improve the bioavailability of other dietary antioxidants such as Annatto. Objective. This study evaluated the effects of egg and annatto-enriched egg consumption on satiety markers and CVD risk factors in healthy adults from Colombia. Methods. A parallel randomized clinical trial was conducted, where one hundred and five (n = 105) men and women, divided into three groups, consumed daily for 8 weeks: (a) two eggs (egg group), or (b) two eggs with annatto (egg + annatto group), or (c) two egg whites (placebo group). RESULTS. The three groups were similar in gender distribution. No significant changes were found over time (before vs. after) in any of the groups nor between the groups in anthropometric variables, physical activity, eating profile, and ghrelin as an objective marker of satiety. In the egg + annatto group, subjective satiety increased (effect size 0.431; p < 0.05) after consumption. Conclusions. In healthy adults, the intake of two eggs, or two eggs with annatto daily for 8 weeks, did not result in significant changes in ghrelin; but eggs with annatto tend to increase the perception of satiety.